النظام القانوني لأملاك الجماعات المحلية العقارية في التشريع الجزائري - لخضر, رضوان (جامعة الوادي -University eloued, 2021)
ولقد اطر المشرع طرق الاستعمال اما استعمالا جماعي مباشر واما استعمالا غير مباشر فالمباشر يستعمله الافراد مباشرة دون اذن من الادارة كالسير في الطريق العام وأما الغير مباشر بواسطة مرفق عمومي يخصص له العقار لتقديم خدمات لصالح العام، اما القسم الثاني من الاستعمال فهو استعمال خاص عادي وغير عادي، فالعادي هو استعمال للأملاك العمومية بشكل انفرادي بواسطة عقد بين الفرد والادارة مقابل دفعه مبلغا مليا كحقوق السوق، أما الاستعمال الخاص للملك العمومي الغير عادي وهو استعمال مكان في ملك عام مخصص لاستعمال الجمهور كقطعة من الرصيف بواسطة قرار اداري منها رخصة الطريق ورخصة الوقوفThe legislator has framed the methods of use either for direct collective use or for indirect use. The direct use is directly used by individuals without permission from the administration, such as walking on the public road. As for the indirect, through a public utility to which the property is allocated to provide services for the benefit of the public. As for the second part of the use, it is an ordinary and unusual private use. The normal is the unilateral use of public property through a contract between the individual and the administration in return for a payment of a sum of money as market rights, while the private use of the extraordinary public property is the use of a place in public property designated for public use as a piece of the sidewalk by an administrative decision, including a road license and a parking permit
قانون عقاري
Keywords: النظام القانوني، لأملاك الجماعات المحلية، العقارية ، التشريع الجزائري; The legal system, the property of local communities, real estate, Algerian legislation